Evaluation of Mean Platelet Volume in Patients of Recurrent Aphthous Stomatitis: Mean Platelet Volume in Patients of RAS - Nadeem, Mujtaba; Manzoor, Usman; Tariq, Uzma; Ahmed, Sufyan; Akbar, Awais; Aijaz Ali Zaidi, Syed (Pakistan Journal of Health Sciences, 2023)
One of the most prevalent conditions affecting the oral mucosa is recurrent aphthous stomatitis (RAS), which is characterized by uncomfortable ulcerations on the movable or non-keratinized oral mucosa. Objective: To compare mean platelet volume (MPV) in patients of recurrent aphthous stomatitis (RAS) versus healthy control. Methods: This non-probability sampling case-control research included 56 RAS patients and 56 healthy controls. Patients who presented for dental treatment and have RAS in oral cavity were included. Patients with systemic inflammatory illnesses, autoimmune diseases like pemphigus, or infectious diseases like herpes who attended for dental treatment and exhibited RAS in the oral cavity were excluded. The healthy control group had no mouth ulcers or blood problems. A Student t-test compared MPV between cases and controls based on age, gender, and MPV. Results: The mean age of the participants was 29.35 ± 8.28 years, with 57 (50.89%) females and 55 (49.11%) males. The mean MPV in the RAS group (8.86 ± 0.33) was significantly higher (p < 0.001) than in the control group (6.95 ± 0.2). The univariable model coefficient of 1.91 (95% CI = 1.81-2.01, p < 0.001) indicates that the RAS group had a significantly higher MPV than the Control group. For gender, males had a lower MPV compared to females (β = -0.36), but it was not statistically significant (p = 0.056). Conclusions: RAS patients have higher platelet activity indicated by higher mean platelet volume (MPV) than healthy controls.